EL GENERO KURTZIANA FRENGUELLI: SU MORFOLOGIA Y VINCULACIONES (Ameghiniana, 2013)
THE GENUS KURTZIANA FRENGUELLI: MORPHOLOGYAND RELATlONSHIPS.- In this paper the morphology of the leaf-genus Kurtziana frenguelli is analized. The cuticle is descríbed for the first time. The generic and specific diagnoses are emended. Comparisons with Pteridophylla Alethopterideae and several Mesozoic leaf-genera are accomplished. It is concIuded that the greater affinities are established with Compsopteris adzvensis and Paehypteris.